Business Sustainability: Efforts To Strengthen Sustainability Corporate In Industrial Estate - Sri Sarjana; Nur Khayati; Lis Warini; Praswiyati Praswiyati (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
Regional development and sustainable development can be done through strengthening various business units developed in certain industrial areas. Industrial estate development is expected to be able to refer to sustainable development by taking into account economic, social, ecological functions and complying with applicable regulations to improve business performance in manufacturing industry. The need for sustainable development in management of industrial estates, diversity of business units, and increasing distribution and management of value chains for business units need to be followed up more comprehensive. Integration of transportation, communication and trade networks in the form of modern logistics and supply chain management enables the production and distribution of global systems that can truly change the level of people's welfare. This research was conducted in three best industrial estates in Indonesia to be taken into consideration in development of 14 priority industrial estate outside the island of Java which has been declared by government. Corporate sustainability important to contribution in improving business performance in manufacturing industry, and will get optimal results if fully supported by diversification strategies, supply chain management and innovation strategies. This research is expected to contribute ideas especially related to business in industrial estates and urban development so that it can further increase understanding of the concepts studied through business performance and its impact on the company's sustainability in development of industrial estates.